Classification of sciences and other areas of knowledge, a problematization - Morales Jasso, Gerardo; Rodríguez López , Abel; Saury de la Garza , Cynthia Ileana (IE Revista de Investigación Educativa de la REDIECH, 2021)
This theoretical article aimed at university education takes up different backgrounds of knowledge classification systems to overcome redundant or anachronistic systems that hinder interdisciplinary work and transversal curriculum. For this, the goal is to generate a better understanding of the organization of knowledge in order to differentiate between sciences, technologies, humanities, arts and services, as well as to make it clear that a single profession can encompass all of them. In addition, it captures a contemporary reality: technoscience. This allows to explain the diversity of existing institutional classifications and to propose the overcoming of anachronistic classifications, because the advancement of knowledge affects its relationship with other areas and its own classification.